Behaviors of 6:2 fluorotelomer sulfonamide alkylbetaine (6:2 FTAB) in wheat seedlings: Bioaccumulation, biotransformation and ecotoxicity - Huanting Zhao; Liping Yang; Xiaojing Yang; Shuyan Zhao (Ecotoxicology and Environmental Safety, 2022)
As a new alternative to perfluorooctane sulfonate (PFOS), 6:2 fluorotelomer sulfonamide alkylbetaine (6:2 FTAB) has been currently used in industrial and consumer applications, which has been frequently detected in environment media. However, the behaviors of 6:2 FTAB in plants are still unclear. This study investigated the bioaccumulation, biotransformation and ecotoxicity of 6:2 FTAB in wheat (Triticum aestivum L.) by hydroponic exposure. 6:2 FTAB was easily taken up by roots with the root concentration factor (RCF) as high as 94.8, but difficult to be acropetally translocated in the shoots with the translocation factor (TF) as low as 0.058. Two intermediates and six terminal perfluorocarboxylic acid (PFCA) metabolites were detected in roots and shoots. The detected metabolites included 6:2 fluorotelomer sulfonic acid (6:2 FTSA), 6:2 fluorotelomer carboxylic acid (6:2 FTCA), perfluoroheptanoic acid (PFHpA), perfluorohexanoic acid (PFHxA), perfluoropentanoic acid (PFPeA), perfluorobutyric acid (PFBA), pentafluoropropionic acid (PFPrA) and trifluoroacetic acid (TFA), and 6:2 FTSA was the main metabolite. 6:2 FTAB significantly reduced the biomass of plant and prevented chlorophyll (Chl) accumulation, while caused no significant change in malondialdehyde (MDA) content. Significant reduction in glutathione (GSH) contents, excess production of reactive oxygen species (ROS), and obvious inhibition of superoxide dismutase (SOD), catalase (CAT), peroxidase (POD) and glutathione-s-transferase (GST) activities were observed, suggesting damage of antioxidant defense systems and failure to detoxication of 6:2 FTAB in wheat. These findings provide important knowledge for the fate of 6:2 FTAB in plants.